On formation flying in low earth mirrored orbits — A case study. (July 2021) - Parsay, Khashayar; Yienger, Kenneth; Rowland, Douglas; Moore, Thomas; Glocer, Alex; Garcia-Sage, Katherine
Abstract: Spacecraft formation flying in co-planar identical orbits with oppositely directed apse lines (eccentricity vectors) allows simultaneous in-situ measurements in different altitudes and time-sequential measurements in a limited altitude range (rapid revisit); a key enabling factor in understanding many poorly understood phenomena in our atmosphere and its interaction with the magnetosphere. The dynamics and control problem for flying formations in mirrored orbits are investigated using the Mechanisms of Energetic Mass Ejection - Explorer (MEME-X) mission concept as a case study. It is determined that the proposed two-craft and four-craft configurations require routine maintenance to correct their relative motion. The formation maintenance costs are quantified for both configurations and determined to be within the capabilities of small satellites. A high-fidelity end-to-end simulation is developed to model the entire two-craft mission concept, from orbit insertion to decommissioning, providing an approximate baseline for the flight dynamics costs of similar missions using multiple spacecraft flying in mirrored orbits. Highlights: Spacecraft formation flying in mirrored orbits is investigated. The dynamics and control of two-craft and four-craft geometries are explored. The proposed formation-keeping strategies are verified for a novel mission concept. The formation-keeping costs are quantified for both formation configurations.